Eco prefab energy independent: green houses - Nowak, Ewa (2014)
Project is composed of different types of single family houses. Every of them are connected by one platform and green transparent gate, which surround all buildings. The gate is open and in esthetical way not disturb the environment. It’s a part of the green briefforedesign.The platform is used as a green space(green roof, terrace). Under the platform exist an interiorroad for the inhabitants. Inside there is a half common half pubic garden, which include small wind turbines to produce common electricity.Each building is different in shape, contrary to the typical anonymous archhitecture. All buildings are part and parcel of one community organism, with integral energy grids, which balance needs and axces capacity.